Financial Contribution of Sharia Philanthropy to Sustainable Social Development - Maskur, Maskur; Hidayat, Deden; Osmiati, Osmiati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the contribution of Sharia finance, particularly Islamic financial philanthropy, to sustainable social development and identifies strategic measures required to enhance its effectiveness. Sustainable social development demands an inclusive economic system that promotes social justice, equitable wealth distribution, and long-term community welfare. Islamic finance, grounded in ethical values and principles of social solidarity, provides redistributive instruments such as zakat, waqf, infaq, and sadaqah that can support these objectives. This research employs a qualitative literature study approach by reviewing and analyzing relevant sources, including academic journals, classical Islamic texts, and scholarly publications related to Islamic finance and sustainable development. Through a systematic examination of the literature, this study explores the conceptual and practical linkages between Islamic financial philanthropy and sustainable social outcomes. The findings reveal that Islamic financial philanthropy plays a significant role in poverty alleviation, economic empowerment, and social inclusion. However, its potential to foster sustainable development depends on effective strategic implementation. Recommended strategies include designing programs aligned with community needs, strengthening collaboration with governmental and private institutions, expanding regional and international partnerships, and improving data management systems to ensure transparency and accountability. Through these measures, Sharia finance can contribute more effectively to sustainable and inclusive social development.